Diverse bodies, Diverse Tits. Artistic action to raise awareness of gender equality and sexual diversity through ceramics: Acción artística para sensibilizar en igualdad de género y diversidad sexual a través de la cerámica (Revista Apotheke, 2021)
In this photo essay, we present the development of an artistic action called Diverse Tits. It was carried out during the month of October 2020 with students of the Degree in Primary Education from the Faculty of Teaching at the University of Valencia. This action is part of a research process to analyse and assess the role of artistic actions in awareness-raising processes regarding issues of gender identity and sexual diversity. The experience consists of reflecting on the diversity of our bodies, from an ecofeminist perspective, to vindicate the need of a more humanized, naturalized, egalitarian, respectful of diversity and inclusive institution. This embodied reflection uses the modelling of anthropomorphic clay pots inspired by the artworks of Emma Low as a way to confront the personal experiences of our body. The results consist of multiple awareness actions through the delivery of micro-stories that accompany these objects. Presents to teaching, research administration and services staff of the University.